Educational program on global warming in the development of environmental awareness in students of a public educational institution - Mejia-Aguirre, Yeni Y. (2022)
Objective: To demonstrate the effectiveness of the application of an educational program on global warming in the development of environmental awareness in 5th and 6th grade students of the I. E. No. 84062 of the district of Cochabamba, province of Huacaybamba, department of Huánuco (Peru). Methods. The approach was quantitative, the type of research was explanatory, experimental and the design was pre-experimental. A previously validated questionnaire was applied. The inferential test applied was Student's t-test. Results. In the initial test before the application of the program, 72% (18) of the students had a high percentage of lack of knowledge (72%). Likewise, at the end of the program, 96% already knew about global warming. Regarding skills, before the application of the program 72 % had low skills, after the program 88 % had high skills regarding environmental awareness. Conclusions. The educational program on global warming is effective in the development of environmental awareness of the sample under study.